From genes to genomes : - Dale, Jeremy (John Wiley & Sons, 2007)
Rapid advances in a collection of techniques referred to as gene technology, genetic engineering, recombinant DNA technology and gene cloning have pushed molecular biology to the forefront of the biological sciences. This new edition of a concise, well-written textbook introduces key techniques and concepts involved in cloning genes and in studying their expression and variation. The book opens with a brief review of the basic concepts of molecular biology, before moving on to describe the key molecular methods and how they fit together. This ranges from the cloning and study of individual genes to the sequencing of whole genomes, and the analysis of genome-wide information. Finally, the book moves on to consider some of the applications of these techniques, in biotechnology, medicine and agriculture, as well as in research that is causing the current explosion of knowledge across the biological sciences.